Investigating the perception of the use of automated valuation models to appraise residential properties in Pretoria, South Africa - Thebe, Moloedi Andries (Department of Construction Economics and Management, 2025)
Purpose of this paper: The study aimed to examine the awareness, knowledge, and perception of the property valuers practicing in Pretoria regarding using the AVMs as a tool to appraise residential properties. Design/methodology/approach This research used a quantitative approach method to assess the level of awareness and knowledge about the appraisal of residential properties using the automated valuation models (AVMs). The research aimed to determine if AVMs outperform traditional valuation methods and assess the implications of their fully automated nature on the valuation profession. A semi-structured online survey was used to collect data from property valuers in Pretoria. The survey was distributed through the South African Council for the Property Valuers Profession (SACPVP) and the South African Institute of Valuers (SAIV), with the survey link sent directly to the targeted participants. Findings According to this research, AVMs have been shown to be more reliable, faster, efficient, and cost-effective than traditional valuations. Conversely, some valuers have reservations about using AVMs for residential properties due to limitations such as the inability to physically inspect properties and the risk of insufficient and unverified data. Furthermore, there are concerns about the potential impact of AVMs on the valuers' profession, as they may become obsolete in the future. Despite these concerns, most valuers who participated in the study believe that AVMs are still a preferred method for evaluating residential properties. Research limitations The study was limited by the POPI Act, resulting in fewer participants than anticipated. The Act establishes specific restrictions for sharing personal information without the owner's consent, preventing direct access to participants. The researcher distributed questionnaires through SACPVP and SAIV services using an online survey. These institutions own the database of all registered valuers in South Africa, making it crucial to work through them to comply with the POPI Act and ethical considerations. Value of paper INVESTIGATING THE PERCEPTION OF THE USE OF AUTOMATED VALUATION MODELS TO APPRAISE RESIDENTIAL PROPERTIES IN PRETORIA, SOUTH AFRICA iv | Page This study aimed to assess the awareness and knowledge of property valuers in Pretoria regarding the use of AVMs in residential property valuation. Additionally, the study sought to determine the extent of AVM usage and its effects on traditional property valuation methods. The paper provides valuable insights by gathering the opinions and perceptions of valuers on the hypothesis surrounding AVMs. Conclusions The results of this study confirm that most of the participating valuers in Pretoria believed that AVMs are the best approach for valuing residential properties due to their efficiency, expediency, and cost-effectiveness, despite some notable concerns raised by the few participating valuers. Although, the conclusion remains that AVMs are the preferred method of valuing residential properties. Keywords: Automated Valuation Models, Fast, Reliable, Accurate, Cost-effective. property inspection.